THE SAVINGS-TRADE-FISCAL GAP MODEL: APPLICATION IN SELECTED WEST AFRICAN STATES - Obukohwo, Efayena Oba; Ngozi, Buzugbe Patricia (Studies and Scientific Researches. Economics Edition, 2017)
With most African economies experiencing adverse economic misalignment in recent times, the need of enhancing the growth process cannot be overemphasized. Using a typical Savings-Trade-Fiscal Gap Model, the paper employed panel data estimation method to examine the impact of savings, trade and fiscal gap on economic growth of 15 West African countries. The paper finds a negative relationship between net trade and economic growth, while savings and government expenditure impacts positively on economic performance. The paper thus, among recommended that it is appropriate for all countries to eliminate fiscal dominance from monetary policy-making, reduce public debt and establish institutions that promote and encourage counter-cyclical fiscal policy, develop their financial systems, establish credibility in fiscal and monetary policy-making as well as encourage trade.